Seismic isolation technology of shallow buried large section utility tunnel with soft soils in seismically vulnerable area - Wang, Zhigang; Chang, Lijun; Ma, Huabing; Zhu, Li; Cui, Guangyao; Shan, Hongwei; He, Ziyang (Frontiers in Earth Science, 2024)
Shallow utility tunnels with exceptionally large cross-sections in weak soil can face significantly more severe seismic risks compared to conventional deep tunnels in seismic hazard areas. This study investigates the seismic response and isolation technologies applied to a large section utility tunnel with 4 compartments in one layer, employing seismic simulations. The engineering context, dynamic motions, and measuring points of the numerical simulation were introduced. Subsequently, the finite element method was employed to explore the seismic behaviors of the large section utility tunnel when subjected to strong earthquake excitations under four conditions. The study explored and comparatively evaluated the seismic isolation effectiveness of three proposed schemes: the grouting scheme, the buffer layer, and the assembly of three-quarters buffer layer, cushion and grouting. The analysis included various indexes such as the deformation, the principal and shear stress, and the safety factor. The finding reveals that the assembly seismic scheme exhibits the most significant seismic effect (95.39%), followed by the buffer layer (38.82%), and the grouting scheme (25.66%). The assembly seismic scheme is recommended for the seismic design in the current large-section utility tunnels. These conclusions provide valuable scientific guidance for the seismic design of large-section utility tunnels, aiding in enhancing earthquake resilience.